(untitled) (Journal of Human Sciences, 2022)
The geographic nature has forced to Braga region, as well as the efforts of “The Sounusi” movement in facilitating a safe trade route with the country of Sudan, dictated the coincidence with the cumulative experience of the majority of the components of its society involved in that trade. The eastern way that started from Benghazi through (Jalo ,Oujela, and Alkufrah) in (Abasha) “the current Chad” was the targeted path as well. Also, the continuance of exchanging the local Arabic and the national goods between the two sides through this path. However, Benghazi Administration was paid an attention by the local people know the western Tripoli state and Tunisian trademen who were proved in the sample of the prior evidence were not shown, but found in Tunisia. Thus , this sample of private evidence in the file of “the Agent” of Tunisia at Benghazi. This research shows “the agent’s performance in Benghazi and analyze his non- shown reports and letters about the administration’s economic and health conditions, in addition of the Tunisian legacy in Benghazi In sort of that it was the Tunisian trade-men legacy from (Jarba and S’faques) who learn trading with (Wadai). The magnificent of trading and the value of Tunisian trade- men legacy , the European voyagers who cross this path to get into (Wadai) , has arise a conflict between the “agent” of Tunisia before the orphans fund , the treasury of Tripoli State and the legacy of Benghazi to have this legacy or not. The objectives of this research focuse on the study of Tripoli relations field, The Tunisian - Benghazi legacy in the seventies of the nineteenth century.